Incríveis legados da 'reforma universitária' de 1968 - Minto, Lalo Watanabe [UNESP]; Minto, César Augusto (My University, 2012)
This article examines aspects of policies for higher education during the Brazilian civil-military dictatorship (1964-1985) and some of its legacies that persist in the decades of 1990 and 2000. The text was divided into two parts: the first one analyses the "university reform" of 1968 and its historical context; the second discusses how some features configure certain trend in policies for higher education, with traces maintained until today. Finally, this amazing continuity is evaluated through four axes of analysis – 1) Fragmentation of education and different access to the levels and stages of teaching; 2) Deformation of the inseparability of teaching, research and extension; 3) Privatization as official policy for higher education; 4) Authoritarianism and systematic repression in institutions of higher education – and it is supported the need to resist and be opposed to the dominant project of policy for higher education in Brazil.

Este artigo analisa aspectos das políticas para o ensino superior brasileiro no período da ditadura civil-militar (1964-1985) e alguns de seus legados, que persistem nas décadas de 1990 e 2000. O texto foi dividido em dois segmentos: no primeiro, aborda-se a “reforma universitária” de 1968 e seu contexto histórico; no segundo, discute-se como algumas características configuram determinada tendência nas políticas para o ensino superior, com traços mantidos até os dias atuais. Por fim, faz-se um balanço dessa incrível continuidade por meio de quatro eixos de análise – 1) Fragmentação da educação e acesso diferenciado a níveis e etapas do ensino; 2) Descaracterização da indissociabilidade ensino, pesquisa e extensão; 3) Privatização como política oficial para o ensino superior; 4) Autoritarismo e repressão sistemática nas instituições de ensino superior – e defende-se a necessidade de resistir e contrapor-se ao projeto dominante de política para o ensino superior no Brasil.
Keywords: Ensino Superior; Reforma Universitária; Ditadura Civil-Militar